Treatment of Morell Lavallee Lesion (MLL) with Arthroscopy - Kandel, Rupak; Zhang, Dezhi; Liu, Danping; Ma, Wen; Guo, Zhanpeng; Zhang, Yuqiang; Yam, Gurung; Wang, Qian (Journal of Karnali Academy of Health Sciences, 2018)
Background: Previous approval for treatment of persistant Morell lavallee soft tissue degloving lesion has included open debridement or simple compression or serial aspiration under USG guidance or insertion of surgical vacuum or sclerodesis with tetracycline/doxycycline. None of them had proven the minimally invasive surgical technological effect of arthroscopy.Purpose of study: This study evaluates the minimally invasive surgical effectiveness and use of radio frequency ablation under arthroscopy for treatment of persistant Morell lavallee soft tissue degloving lesion. This technique provides satisfactory cosmetic and functional effect as overall outcome.Methods: We treated 7 cases of persistant Morell lavallee lesion between Nov 2010 to March 2013. These lesions developed in 5 male and 2 female patients (Mean age 36.57yr, Range 23-48 yrs) due to various mode of trauma. The lesion involved the thigh region in 3 patients with gluteal, distal leg, knee and forearm being other region involved. An area of palpable fluctuance was the most coherent examination finding. MRI and Ultrasonography confirmed the diagnosis with clinical evidences. Treatment was achieved by placement of arthroscope, aspiration of fluid and radio frequency ablation of inner layer of capsule and proceed with compressive elastic bandaging. Healing was defined as the loss of fluctuation with complete absence of fluid on ultrasonography (USG).Result: The average duration of the persistence of the lesion was 3 month. All lesions were evacuated arthroscopically and found to be negative on culture. The mean follow up period was 11 month (Range 6-24 month). All patients showed complete resolution of fluid collection and no contour deformity at final follow up. All the lesions healed exclusive of any infections or other complication. No recurrences were detected during the follow up period. A persistent feeling of tightness was the most common problems faced on long term follow up.Conclusion: The persistant closed degloving lesion can be managed easily, conveniently and effectively with radio frequency ablation under arthroscopy. Patients were satisfied with cosmetic problems like contour deformity, tightness of skin, rough scar mark, diminished sensation and skin mobility at site of lesion.